Cognitive deficits in treatment-resistant depression: protocol for a systematic review and meta-analysis - Maximilian Kiebs; Richard Porter; Katie Douglas; Eivind Haga Ronold; Daniel Jensen; Anders Lillevik L Thorsen; Rune Raudeberg; Leif Oltedal; Åsa Hammar; Marco Hirnstein (BMJ Open, 2025)
Introduction Major depressive disorder (MDD) is a major global healthcare challenge. This is, in part, due to the lack of treatment response and chronic course of MDD. Such a course of illness is often termed treatment-resistant depression (TRD) and is seen in over one-third of people with MDD. Reasons for treatment resistance are not well established, nor is the definition of TRD. Duration and severity of depression, however, are associated with TRD and are also associated with cognitive deficits. Thus, TRD could be particularly prone to cognitive deficits and at heightened risk for neuroprogression. While the cognitive profile of MDD has been investigated in several systematic reviews, no systematic review of cognition in TRD exists to date. The present study will fill this gap in the literature. It is expected that TRD will show more severe cognitive deficits than generally reported in MDD and deficits in all cognitive functions are expected.Methods and Analysis A systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines will be performed of the databases Embase, Pubmed/MEDLINE, PsychINFO and Cochrane including peer-reviewed studies on humans using standardised cognitive tests. Pilot searching was performed in January 2025 and the full search will be commenced in June 2025, with additional searches following completion. Where sufficient data are reported, a meta-analysis comparing deficits in TRD with MDD and healthy control participants will be performed; alternatively, effects based on norms will be calculated. Meta-regression, subgroup and sensitivity analyses will be conducted to explore moderators that are sufficiently reported in the literature. The quality of studies will be assessed by the Newcastle-Ottawa Scale.Ethics and dissemination Ethical approval is not necessary to perform the study, and results will be presented at a suitable conference and published in a peer-reviewed journal.Prospero registration number CRD42024538898.